Interpretation and Dissemination Strategies of the Significance of Dragon and Lion Dance Courses in Cross-Cultural Communication from the Perspective of Cultural Semiotics - Zhang Xinyi; Huang Da (SHS Web of Conferences)
This paper explores the significance and dissemination strategies of dragon and lion dance courses in cross-cultural communication from the perspective of cultural semiotics. Dragon and lion dances, as important symbols of traditional Chinese culture, carry rich cultural connotations and have strong potential for cross-cultural dissemination. Through the theoretical framework of cultural semiotics, this article analyzes the symbolic significance of dragon and lion dance as cultural symbols and its role in global cultural exchange. The paper first reviews the basic theories of cultural semiotics, explores the interaction between symbols, cultural backgrounds, and social meanings, and then analyzes how dragon and lion dance courses promote cultural identity and understanding through the interpretation and adaptation of symbols in cross-cultural environments. In addition, this article also proposes communication strategies for dragon and lion dance courses, including the integration of the education system, the application of modern communication media, cultural adaptation and localization strategies, as well as cross-cultural cooperation and interaction. These strategies not only contribute to the global dissemination of dragon and lion dance courses, but also promote the recognition and dissemination of Chinese culture around the world. Finally, the paper summarizes the importance of dragon and lion dance courses in cross-cultural communication and looks forward to their future development directions. With the deepening of global cultural exchange, the dissemination of dragon and lion dance courses will become more efficient and an important platform for promoting global cultural understanding and cooperation.